The Effect of Repeated Lockdowns during the Covid-19 Pandemic on UK Mental Health Outcomes - Joanne Lindley; Cinzia Rienzo (Global Labor Organization (GLO), 2021)
This paper assesses the impact of the Covid-19 lockdown measures on the mental health of individuals in the UK, starting from the early restrictions in April 2020, and covering three subsequent lockdowns, up until March 2021. It also considers three aspects of mental health; that is 'anxiety and depression', 'social dysfunction', and 'loss of confidence', in order to identify which specific dimensions of respondents' psychology have been adversely affected. Our findings show that women appear to be more sensitive to the effect of the pandemic, and report much higher levels of anxiety and depression than males; whilst social dysfunction appears to be a more permanent fixture. Initially, social dysfunction was higher for women and younger workers, but it remained high for women and the over 55s. Consequently, our evidence supports targeted policies aimed at reducing social isolation for women and older workers. Finally, we show that financial difficulties had a growing impact on all mental health outcomes, as the pandemic progressed.
Keywords: I30; I10; 330; Covid-19; mental health; subjective financial wellbeing